Oral health status and factors associated with oral health of primary school children in Gulu district, northern Uganda - Akera, Peter; Kennedy, Sean E; Lingam, Raghu; Richmond, Robyn; Schutte, Aletta E (BMC, 2024)
Globally, oral diseases remain a major public health problem. However, there is limited information about the oral health status and factors associated with oral disease among children in Uganda. The aim of this study was to examine the oral health status and factors associated with oral health of primary school children in urban and rural areas of the Gulu district of northern Uganda.BACKGROUNDGlobally, oral diseases remain a major public health problem. However, there is limited information about the oral health status and factors associated with oral disease among children in Uganda. The aim of this study was to examine the oral health status and factors associated with oral health of primary school children in urban and rural areas of the Gulu district of northern Uganda.A comparative cross-sectional study was conducted among 356 school children aged 11-13 years attending six schools located in urban and rural areas. The children received a clinical oral examination and participated in a questionnaire survey that collected information on sociodemographic and oral health knowledge, attitude, and practices. All data were entered and analysed using IBM SPSS Statistics for Windows, Version 26.0. Armonk, NY: IBM Corp statistical software. Logistic regression analyses examined factors associated with dental caries and gingival bleeding.METHODSA comparative cross-sectional study was conducted among 356 school children aged 11-13 years attending six schools located in urban and rural areas. The children received a clinical oral examination and participated in a questionnaire survey that collected information on sociodemographic and oral health knowledge, attitude, and practices. All data were entered and analysed using IBM SPSS Statistics for Windows, Version 26.0. Armonk, NY: IBM Corp statistical software. Logistic regression analyses examined factors associated with dental caries and gingival bleeding.Of the 356 children (11-13 years) included, the mean age was 12.2 years, 140 (39.3%) were male and 176 (49.4%) were from urban areas. The proportion of school children with dental caries was 33.6% (n = 119), with the mean decayed, missing due to caries, and filled teeth (DMFT) index of 0.81 (25th percentile = 0; 75th percentile = 1.00). There was no significant difference in caries prevalence between rural and urban children (31.6% versus 35.6%, p = 0.33). Of the children involved in the study, 141(39.8%) had gum bleeding. The mean oral knowledge score was 2.85 ± 1.53 (range, 0-7), while the mean attitude, hygiene practice, frequency of sweets consumption, and oral health related impact scores were 4.25 ± 1.23 (range, 1-6), 5.40 ± 1.81 (range, 0-9), 25.66 ± 4.29 (range 9-54) and 2.1 ± 1.65 (range, 0-6), respectively. Using logistic regression analyses, as oral health knowledge score increased the odds of not having dental caries increased (aOR = 1.19, 95% CI 1.02-1.39).RESULTSOf the 356 children (11-13 years) included, the mean age was 12.2 years, 140 (39.3%) were male and 176 (49.4%) were from urban areas. The proportion of school children with dental caries was 33.6% (n = 119), with the mean decayed, missing due to caries, and filled teeth (DMFT) index of 0.81 (25th percentile = 0; 75th percentile = 1.00). There was no significant difference in caries prevalence between rural and urban children (31.6% versus 35.6%, p = 0.33). Of the children involved in the study, 141(39.8%) had gum bleeding. The mean oral knowledge score was 2.85 ± 1.53 (range, 0-7), while the mean attitude, hygiene practice, frequency of sweets consumption, and oral health related impact scores were 4.25 ± 1.23 (range, 1-6), 5.40 ± 1.81 (range, 0-9), 25.66 ± 4.29 (range 9-54) and 2.1 ± 1.65 (range, 0-6), respectively. Using logistic regression analyses, as oral health knowledge score increased the odds of not having dental caries increased (aOR = 1.19, 95% CI 1.02-1.39).The prevalence of dental caries and gum bleeding of primary school children in Gulu district is high. Children lacked knowledge on causes of oral disease, and behaviour towards oral disease prevention. In addition, oral health knowledge scores were significantly associated with dental caries. Oral health education programs in schools should emphasise providing skills-based education.CONCLUSIONThe prevalence of dental caries and gum bleeding of primary school children in Gulu district is high. Children lacked knowledge on causes of oral disease, and behaviour towards oral disease prevention. In addition, oral health knowledge scores were significantly associated with dental caries. Oral health education programs in schools should emphasise providing skills-based education. MEDLINE - Academic